1996
DOI: 10.2172/392800
|View full text |Cite
|
Sign up to set email alerts
|

Water supply at Los Alamos during 1994. Progress report

Abstract: I ICover illustration: The graph illustrates the changes in water levels observed in the test welki in the main aquifer of the Los Alamos area. These changes indicate declines of as much as 35 feet. Water level changes in pumping well fields are discussed in Section V of this report. An Afirmative Acfion/Equal Opportunity Employer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…More than 50 active and inactive water‐supply and test wells intersect regional groundwater across the Pajarito Plateau (Griggs, 1955, 1964; Cushman, 1965; Cooper et al, 1965; Purtymun et al, 1990, 1995a, 1995b; Purtymun, 1995; Stoker et al, 1992; McLin et al, 1996, 1998; John Shoemaker, Inc., 1999; Koch and Rogers, 2003). Depth to water is greatest at mesa‐top locations in the western part of the plateau (e.g., 375 m, 1245 ft, at Well CdV‐R‐15‐3) and decreases eastward.…”
Section: Geologic Setting Of Groundwater Occurrencesmentioning
confidence: 99%
“…More than 50 active and inactive water‐supply and test wells intersect regional groundwater across the Pajarito Plateau (Griggs, 1955, 1964; Cushman, 1965; Cooper et al, 1965; Purtymun et al, 1990, 1995a, 1995b; Purtymun, 1995; Stoker et al, 1992; McLin et al, 1996, 1998; John Shoemaker, Inc., 1999; Koch and Rogers, 2003). Depth to water is greatest at mesa‐top locations in the western part of the plateau (e.g., 375 m, 1245 ft, at Well CdV‐R‐15‐3) and decreases eastward.…”
Section: Geologic Setting Of Groundwater Occurrencesmentioning
confidence: 99%
“…Based on streamflow data and transient head data, basin‐scale inverse modeling (Keating et al, 2003) indicated that approximately 253 kg s −1 of the gain to the river along this reach originated on the Pajarito Plateau and the Sierra de los Valles. This analysis probably underestimates total recharge on the plateau, in part, because the basin model was calibrated to a lower estimate of aquifer discharge north of Otowi Bridge than is indicated by the streamflow analysis presented in the Part of the reason for the differences between these various estimates of total recharge is that several of the smaller estimates (McLin et al, 1996; Speigel and Baldwin, 1963; Griggs and Hem, 1964) emphasized the southern portion of the plateau (including LANL), which according to our streamflow analysis in the , is discharging less water than the northern portion of the plateau. Although these various estimates are disparate and reflect real uncertainty, they are extremely valuable as bounding values for flow and transport modeling.…”
Section: Hydrogeologic Settingmentioning
confidence: 94%
“…Many authors have identified the Rio Grande as the discharge point for the regional aquifer (Cushman, 1965; Griggs and Hem, 1964; Hearne, 1985; McAda and Wasiolek, 1988; Purtymun and Johansen, 1974; Theis and Conover, 1962). Previous reports have cited a variety of evidence to support this, including streamflow gain along the Rio (Balleau Groundwater, 1995; Purtymun and Johansen, 1974; Spiegel and Baldwin, 1963), measured vertical upward gradients in the vicinity of the Rio Grande (Cushman, 1965; Griggs and Hem, 1964), the presence of flowing wells (McAda and Wasiolek, 1988; McLin et al, 1996; Spiegel and Baldwin, 1963), and springs along the river (McLin et al, 1996). Discharge to the river may occur as lateral flow, upward flow, or as flow from springs in White Rock Canyon.…”
Section: Hydrogeologic Settingmentioning
confidence: 98%
See 2 more Smart Citations